Economic and social determinants of life expectancy in China - Li, Ruitao; Zhan, Yunqiu; Tao, Yinying; Wang, Rong; Gu, Xiao; He, Zhenhua; Zhu, Bingcheng (Frontiers in Public Health, 2025)
Life expectancy (LEX) is closely linked to SDG 3: Good Health and Wellbeing, which aims to ensure healthy lives and promote wellbeing for all ages. Improving LEX reflects progress in reducing preventable diseases, enhancing healthcare access, and addressing social determinants of health. By focusing on economic growth, education, and healthcare, countries can achieve sustainable improvements in life expectancy, contributing to the broader goals of SDG 3. Previous studies take economic or social determinants of LEX individually. Thus, this study fills the gap to empirically examines the impact of Economic and social determinants of LEX in China from 2000 to 2023. This study utilizes the Autoregressive Distributed Lag (ARDL), Fully Modified Ordinary Least Squares (FMOLS), and Dynamic Ordinary Least Squares (DOLS) estimators. The finding shows that health expenditure (HE), birth rate (BR), and education (EDU) have a positive effect on LEX. On the other hand, inflation (INF), population growth (PG), and mortality rate (MR) negatively affect LEX. This study has several policy recommendations based on findings to enhance the LEX in China.